Cost–consequence analysis of a hemostatic matrix alone or in combination for spine surgery patients. (3rd October 2018) - Ramirez, Manuel G.; Niu, Xiaoli; Epstein, Josh; Yang, Dongyan
Abstract: Background: A five-year retrospective database analysis comparing the use of Floseal 1 flowable topical hemostat alone (F) and in combination with gelatin/thrombin (F + G/T) to achieve hemostasis and control surgical bleeding showed higher resource utilization for F + G/T cases relative to F matched pairs during spinal surgery. Lower resource use in the F group was characterized by shorter hospital length of stay and surgical time as well as fewer blood transfusions and less hemostat agent used per surgery. Objective: To evaluate the cost–consequence of using F compared to F + G/T in minor, major and severe spinal surgery from the US hospital perspective. Methods: A cost–consequence model was developed using the US hospital perspective. Model inputs include clinical inputs from the literature, cost inputs (hemostatic matrices, blood product transfusion, hospital stay and operating room time) from the literature, and an analysis of annual spine surgery volume (minor, major and severe) using the 2012 National Inpatient Sample (NIS) database. Costs are reported in 2017 US dollars. One-way and probabilistic sensitivity analyses address sources of variability in the results. Results: A medium-volume hospital (130 spine surgeries per year) using F versus F + G/T for spine surgeries is expected to require 85 less hours of surgical time, 58 fewer hospital days and 7 fewer blood transfusions in addition to hemostat volume savings (F: 1 mL, thrombin: 1994 mL). The cost savings associated with the hospital resources for a medium-volume hospital are expected to be 317, 959 (surgical hours = 154, 746, hospital days = 125, 237, blood transfusions = 19, 023, hemostatic agents = 18, 953) or 2445 per spine surgery. Conclusions: The use of F versus F + G/T could lead to annual cost savings for US hospitals performing a low to high volume of spinal surgeries per year.